GREEN HOUSE FERTIGATION SYSTEM - Syafiuddin, Nor Syafiqah (Universiti Teknologi Petronas, 2011)
The project is about Green House Fertigation System which the main focus is on watering and fertilizing. The project is meant to efficiently improve the distribution of water and fertilizer inside the green house. It is an intelligent and advanced system where the nutrients (water and fertilizer) can be controlled and distributed based on the time set. The proportion of fertilizer and water used for this project is in 1 : 100 ratio. PIC 16F877A microcontroller is used as the control tmit. The microcontroller will monitor the inputs and as a result the program would tum outputs on and off. The input of this system is the time setting while the output is the water pump that will distribute the nutrient to the plants.